Determinants of financial well-being among young employees in Malaysia - Sabri, Mohamad Fazli; Zakaria, Nurul Farhana; Abdul Rahim @ Abdul Wahab, Husniyah; Othman, Mohd Amim (Institute for Social Science Studies, Universiti Putra Malaysia, 2013)
Current high levels of individual indebtedness and increasing focus on individual responsibility for financial planning shows that there is a growing need for better financial management particularly among the young adults. The purpose of this study is to identify the financial status of young employees in Malaysia, to examine the levels of financial literacy, financial capability, financial problems and financial well-being of young employees and to examine factors affecting financial well-being of young employees. The sample consists of 508 of young employees age 40 and below in central zone of Malaysia, which selected through multi stage sampling technique. Data were collected through self-administered questionnaires. Results of the study showed that the respondents consisted of 195 males (38.4%) and 313 females (61.6%) with mean age of 31.2 years old. Most of the respondents represented high-income group (earning monthly income above RM 3,500 with mean monthly household income RM 4937.66) and had secondary education level. Only 28.0% of the respondents had high level of financial literacy, 73.6% of them had moderate level of financial capability,77.0% had low level of financial problems and 78.5% had moderate financial well-being. Results of Pearson Correlation indicated that there were significant relationships between financial literacy (r= .205**, p≤ 0.01), financial problems (r= -.565**, p≤ 0.01), financial capability (r= .358**, p≤ 0.01) with financial well-being. The multiple regression results showed that there was an influence of demographic characteristics (household income) toward financial well-being of young employees. Financial literacy, financial problems and financial capability had significant influence toward financial well-being whereby financial problems become a major contributing factor to the financial well-being (r2 =.455, p=.000). By understanding more about the factors that hindering and promoting the financial well-being, it is hoped to help young employees to become financial prudence and in the long-run could decrease the number of young employees declared bankruptcy.